Shariah resolution on practice note for sell and buy back agreement - Che Seman, Azizi; Hasan, Aznan; Hassan, Rusni; Mohamad, Shamsiah (AIBIM, 2025)
The Treasury and Market Committee (TMC) has proposed developing a Practice Note for Sell and Buy Back Agreements (PN SBBA) to streamline documentation requirements for interbank repo transactions. This initiative simplifies the execution of Shariah-compliant sell and buy-back agreements, aiming to boost activity in the Islamic interbank money market. By standardizing processes, the PN SBBA facilitates quicker turnaround times (TAT) for member banks, enhancing operational efficiency while maintaining rigorous compliance with Islamic finance principles.